IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA ARAB DI MA SUNAN AMPEL BAUJENG - Zahrotul Aini (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
The purpose of this study was to describe the implementation of character education of Arab language learning in MA Sunan Ampel Baujeng include planning, realization, assessment, inhibiting factors and supporting factors felt a teacher. The research of this was descriptive research. The Data include is the interview, inquiry, classroom observation and the analysis of the documentation. Test the credibility of the research is the perseverance observation and the method triangulation. The results of data later analysed by Miles method and Huberman method. The result study of character was after the implementation of learning in the silabus and the RPP include the assessment effective by means of the observation, the matter, and the discussion classical. Supporting factors is family environment, the citizens of the school, society, custom, infrastructure,and the setting a schedule teach. Inhibiting factors is hard the choose and integrate on a learning materials, the value a success education character and the medium of learning is less.